Nitrogen fertilization in maize and xaraés palisade grass under no‑tillage and conventional tillage in an agrosilvopastoral system - Bravin, Maísa Pinto; Oliveira, Tadário Kamel de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the agronomic performance of the maize and xaraés palisade grass (Urochloa brizantha ’Xaraés’) crops in intercropping, grown in no‑tillage and conventional tillage, in an agrosilvopastoral system, with the application of different nitrogen topdressing rates. The experiment was conducted in a maize crop area with the forest species “mulateiro” (Calycophyllum spruceanum). The experimental design was randomized complete blocks, in a split‑plot arrangement with two systems of soil management (no‑tillage and conventional tillage with heavy disk) allocated to the plots and five rates of nitrogen topdressing (0, 50, 100, 150, and 200 kg ha‑1 N) to the subplots, totaling ten treatments. Maize grain yield responded linearly to N application in area of ​​conventional tillage. In no‑tillage area, the dose of 165 kg ha‑1 N topdressing was necessary to obtain satisfactory yields. Nitrogen topdressing in maize crop until the dose of 200 kg ha‑1 N does not influence xaraés palisade grass yield when intercropped between the lines, after maize harvest.